Parotid Gland Comparative Microscopic Anatomy - Roa,Ignacio (Sociedad Chilena de Anatomía, 2019)
SUMMARY: The frequent use of animal models in biomedical research means that the anatomy or histology of the animals is constantly analyzed so the results obtained can be extrapolated to human tissues; therefore, knowledge of the structures studied is truly important. This study compares the human parotid gland to that of three animal species from a histological point of view. Five parotid gland samples from each animal species were used: Sprague Dawley rats (Rattus norvegicus), C57BL/6 mice (Mus musculus) and male rabbits (Oryctolagus cuniculus). The samples were stained using H/E, Masson trichrome and van Gieson’s techniques. The anatomical relations of the parotid glands in the three species were the facial nerve, master muscle and mandibular ramus among other anatomical elements. Histologically, the duct system in the three species is comprised of intercalated, striated, excretory ducts and main excretory ducts. Human, rodent and rabbit parotid glands are made of purely serous adenomeres. The intercalated and striated ducts are prominent. The human parotid gland is well characterized by intralobular adipose tissue, as is observed in rabbit, whereas the adipocytes are not prominent in the parotid gland in rats and mice. The tissue of the rat parotid gland contained a large number of serous acini that included a large area of gland tissue and few ducts, as observed in the rabbit and human. The glands studied present considerable morphological similarities with the human one that make them reliable candidates as experimental models of parotid tissue.